Genetic diversity, population structure, pollen morphology and cross‐compatibility among Chinese Cymbidiums. Issue 1 (5th December 2013) - Li, Xiaobai; Xiang, Lin; Wang, Yan; Luo, Jie; Wu, Chao; Sun, Chongbo; Xie, Ming; Debener, T.
Abstract A total of 85 Chinese Cymbidiums and one Zygopetalum were collected and analysed using 29 simple sequence repeats (SSRs) and 12 intersimple sequence repeats (ISSRs). These Chinese Cymbidiums are some of the most popular cultivars in market. The pairwise genetic distance between these accessions averaged 0.897, ranging from 0.259 to 1.000. A model‐based clustering analysis revealed five genetic groups with serious admixture ancestry, as indicated by a fixation index of 0.156 and only 10.67% genetic variation among groups. By analysing the cross‐compatibility and pollen morphology, Chinese Cymbidiums are revealed to have high compatibility for intra‐ and interspecific crosses. Notably, Zygopetalum mackayi had high compatibility with Chinese Cymbidiums and shared similar morphologies in terms of pollinia and pollen grain. This study is the first to report a successful cross between Zygopetalum and Chinese Cymbidiums. The high compatibility offers the potential for introducing Zygopetalum mackayi's superior traits into Chinese Cymbidiums. The similar pollen morphology as well as the low genetic differentiation might be related to the high cross‐compatibility among these accessions.